Aestheticism as the 'moral' resolving the paradox of wilde's art in his fairy tales - Sioson, Irish C. (The Scholastican Journal, 2016)
The study aimed to determine the identities of Overseas Filipino Workers (OFW) working in Saudi Arabia as revealed in the metaphors they used in their own poems. Twenty-nine poems were examined and results showed that major metaphors employed by OFW to present themselves in poems were: 1)the suffering hero; 2 the Renaissance man; 3) the bank; and 4) the unfaithful. Minor metaphors found in the sample included were: 1) the celebrated hero; 2) the sacrificial lamb; 3) the prisoner; and 4) the unfaithful. Minor metaphors found in the sample included were : 1) the celebrated hero; 2) the sacrificial lamb; 3) the prisoner; and 4) the shopping mall. Among the metaphors used to represent Saudi Arabia, on the other hand were: 1) as promised land; 2 as predators; and 3) as temptation. It was found that biblical recontextualization is a notable feature in these poems. Such metaphors help clarify how the OFWs perceive themselves, and situate these proverbial "new heroes" (bagong bayanin) in the diaspora.